Clearcutting in Maine: Would Somebody Please Ask the Right Question? - Hagan, John (Maine Policy Review, 1996)
In November [1996], Maine citizens will cast their votes for or against the Green Party-initiated referendum on forest practices. Better known as the clearcutting referendum, its supporters and opponents have staked out their terms in what has become a bitter debate over "jobs for Maine people" versus the "future of the Maine North Woods." Yet, amidst the deluge of media campaigns and ideological predictions, rest important questions—about forest management practices and how best to ensure a viable future for the people and forests of Maine. John Hagan contributes a perspective to this debate, blending scientific data with personal experience of the Maine North Woods. He wonders whether we asked enough, or even the right, questions to fully ensure that a "yes" or a "no" vote in November will protect the values we hold for the forests and people of Maine.